Could optical coherence tomography detect monosodium urate crystal deposition at artery walls? An exploratory, phantom-based study - Javier Sánchez-Pujol; José Valencia; Juan-Miguel Ruiz-Nodar; Mariano Andrés (PLoS ONE, 2025)
Objective Some reports suggest monosodium urate (MSU) crystals may deposit in artery walls. This exploratory study evaluated the capacity of optical coherence tomography (OCT) to detect MSU crystals in vessel phantoms. Methods We used 3D-printed blood vessel phantoms made of photosensitive acrylic resins, with varying compliances. 0.1cc volume injections of centrifugated human synovial fluids containing MSU crystals, calcium pyrophosphate crystals or 0.9% saline were performed in four predefined locations in the phantoms. OCT was subsequently performed in a blinded manner by two cardiologists, experts in the technique. Two exploratory definitions for MSU crystal deposits were used, depicting a lesion with high attenuation (#1) or also with a linear morphology (#2). Diagnostic properties of both definitions were studied building 2x2 tables. Results Definition #1 was found by OCT in 3/8 (37.5%) of MSU injections and in 3/16 (18.8%) of controls, what yielded a sensitivity of 37.5%, specificity of 81.3%, positive and predictive values of 50.0% and 72.2% respectively, and positive and negative likelihood ratios of 2 and 0.77. Definition #2 was only seen in 2 cases, both with MSU crystals (8.3%); this definition showed a sensitivity of 25.0%, specificity of 100%, positive and predictive values of 100.0% and 72.7%, a negative likelihood ratio of 0.8, while the positive ratio could not be calculated. Data seemed to be slightly better with Semirigid phantoms. Conclusion This preliminary, preclinical data suggest OCT could detect MSU crystals deposits in vessel walls.